2007
DOI: 10.1063/1.2739336
|View full text |Cite|
|
Sign up to set email alerts
|

Comparison of efficiencies of GaAs-based pulsed terahertz emitters

Abstract: Pulsed terahertz (THz) radiation from the electron-hole plasma excited by a femtosecond optical pulse in GaAs-based emitters is studied by Monte Carlo simulations. The THz energy radiated from the n- and p-doped surface emitters, from the contactless p-i-n emitter, and from the photoconductive emitter is evaluated. It is found that the THz energy radiated by photoconductive emitter exceeds the energy radiated by the surface and p-i-n THz emitters by more than one order. The results of the simulations show that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…The greatest achievements have been reported in the visible and near-infrared ranges, whereas the performance in the terahertz frequency range is still considered modest. Therefore, a new generation of emitters [3,4] and detectors [5,6], based on the construction of the n + /n and n + /i (or p + /i) homojunction, have been proposed for operations in the terahertz range. Although they hold promising characteristics, these devices are still considered experimental in nature due to the underlying physics not being fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…The greatest achievements have been reported in the visible and near-infrared ranges, whereas the performance in the terahertz frequency range is still considered modest. Therefore, a new generation of emitters [3,4] and detectors [5,6], based on the construction of the n + /n and n + /i (or p + /i) homojunction, have been proposed for operations in the terahertz range. Although they hold promising characteristics, these devices are still considered experimental in nature due to the underlying physics not being fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…However, the results in terahertz frequency range are quite modest. Recently new emitters [1,2] and detectors [3] on the base of n + /n and n + /i GaAs homojunctions have been proposed. Nevertheless, despite all the theoretical and experimental research done, the physics of these devices is still under consideration.…”
Section: Introductionmentioning
confidence: 99%
“…In materials with picosecond and sub-picosecond carrier recombination times, the spectral peak of the pulses hits the THz range. Proposed as early as in the 1980s [29], PC emitters are being continuously improved up to now [28,[30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45]. It was found that typically low THz output power (a few hundred nW) and the optical-to-THz conversion efficiency can be increased by overcoming the effects of screening out the bias field by the photoexcited carriers [30][31][32][33].…”
Section: Resonance Polarization Effectsmentioning
confidence: 99%